2016
DOI: 10.4236/ajac.2016.71004
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Investigation of Energetics and Electronic Structures of Ni and Sc Co-Doped MgH<sub>2</sub>

Abstract: First-principles calculations were used to study the energetics and electronic structures of Ni and Sc co-doped MgH 2 system. The preferential positions for dopants were determined by the minimal total electronic energy. The results of formation enthalpy indicate that Ni and Sc co-doped MgH 2 system is more stable than Ni single-doped system. The hydrogen desorption enthalpies of these two hydrides are investigated. Ni and Sc co-doping can improve the dehydrogenation properties of MgH 2 . The lowest hydrogen d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Since, the dissociation of H 2 molecules and diffusion of hydrogen atoms through the metal are two rate limiting steps for H 2 absorption in Mg, several theoretical studies have been conducted to analyze the hydrogen magnesium interaction in respect to the transition metal catalysts [38][39][40][41][42]. Kecik et al [38] used the first principle molecular dynamics method for the calculation of adsorption energies of Mo, Nb, Mn, Cr, Co, Fe, V, Pd, and Ni on a magnesium surface and suggested that the transition metals including and to the left of the VI-A column tend to be adsorbed on a substitutional site while other transition elements have a tendency to be adsorbed on a bridge site.…”
Section: Transition Metal Catalystsmentioning
confidence: 99%
“…Since, the dissociation of H 2 molecules and diffusion of hydrogen atoms through the metal are two rate limiting steps for H 2 absorption in Mg, several theoretical studies have been conducted to analyze the hydrogen magnesium interaction in respect to the transition metal catalysts [38][39][40][41][42]. Kecik et al [38] used the first principle molecular dynamics method for the calculation of adsorption energies of Mo, Nb, Mn, Cr, Co, Fe, V, Pd, and Ni on a magnesium surface and suggested that the transition metals including and to the left of the VI-A column tend to be adsorbed on a substitutional site while other transition elements have a tendency to be adsorbed on a bridge site.…”
Section: Transition Metal Catalystsmentioning
confidence: 99%